The New Historical Narrative in the 19th Century Painting - Chernysheva, Maria A. (Actual Problems of Theory and History of Art, 2018)
The article deals with the new type of historical painting created by Paul Delaroche in the 1830s. The category of narrative is the most important one for understanding the specificity of that type.The narrative model in the classical historical painting is outlined, and the narrative structure of Delaroche’s Cromwell and Charles I is analyzed. The context of the picture is taken into account: its reception by contemporaries, its narrative sources in historical writings of Chateaubriand and Guizot, Guizot’s thoughts about narrative principles in literature and historiography, as well as judgements of contemporaries on Guizot’s historical narrative.It will be evident that in Delaroche’s Cromwell narration is undergoing fundamental changes with respect to its classical model, simultaneously receiving an impulse to its own disappearance. In Cromwell the description, which provides a visible exposition of the scene, displaces the narration proper that gives action to the scene. This action escapes from being identified with this or that “function”, i. e. a type of action in its significance for a plot. Therefore, the action preserves semantic ambiguity and inconsistency. At the same time, and partly due to these qualities, the historical representation acquires closer similarity with the reality.
Keywords: French art of the 19th century; history painting; narrative; Paul Delaroche; François Guizot